Bahasa dan Identitas Sosial Generasi Muda dalam Lirik Lagu Evaluasi: Kajian Sosiolinguistik - Sofia Laila Rahmah; Ade Nandang; Asep Supianudin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2026)
This study examines the relationship between language and youth social identity in the lyrics of the song “Evaluasi” by Hindia from a sociolinguistic perspective. The purpose of this study is to describe the forms of language variation found in the song lyrics and to explain how these linguistic choices represent and construct the social identity of Indonesian youth. This research employs a descriptive qualitative method, with the song lyrics serving as the primary data source. The data consist of the textual lyrics of “Evaluasi”, which are analyzed based on language variation, including the use of non-standard language, slang, code-mixing, and linguistic repetition. Data analysis is conducted through identification, classification, and interpretation by relating linguistic findings to the social context of urban youth. The results indicate that the use of non-standard language and slang functions as a linguistic strategy to establish emotional closeness and to reinforce youth group identity. Furthermore, linguistic repetition reflects processes of self-reflection and internal conflict experienced by young people in response to social pressure and life uncertainty. Language variation in the lyrics does not merely serve an aesthetic function but operates as a social practice that represents the experiences, emotions, and social positioning of contemporary youth. This study concludes that the lyrics of “Evaluasi” can be understood as a social text that captures the dynamics of youth social identity in Indonesia. The findings are expected to contribute to sociolinguistic studies, particularly in understanding the role of language in popular music as a medium for social identity construction.